RELIGIOUS EXPRESSION OF ISLAMIC ART AS A MEDIUM OF DA'WAH: A LITERATURE STUDY - Mochammad Afif Jalla; Abdul Muhid (Journal International Dakwah and Communication, 2026)
Islamic art is an effective medium of proselytization in conveying the spiritual and moral values of Islam to society. Islamic arts, such as calligraphy, mosque architecture, music, and poetry, not only have aesthetic value but also contain deep religious messages. However, in the era of globalization, Islamic art faces challenges such as the influence of global culture and technology, so it needs to be further explored to ensure its relevance. The purpose of this study is to analyze religious expression in Islamic art and its potential as a medium for da’wah, as well as identify challenges and opportunities in the contemporary era. The method used is a literature study with a qualitative approach, collecting and analyzing academic sources such as journals, books, and reliable articles. The results showed that Islamic art plays an important role in building spiritual identity, facilitating character education, and bridging intercultural dialogue. Key findings include the effectiveness of Islamic art in da’wah, its adaptation to digital technology, and its synergy with local values. In conclusion, Islamic art is a powerful and multifunctional medium for da’wah, which needs to be preserved and developed to remain relevant amidst the dynamics of the times. Recommendations include training for artists and preachers, as well as collaboration between stakeholders to support innovation in Islamic arts.